Pola Pembentukan Konstruksi Verba Serial dalam Bahasa Batak Toba (Teori X-Bar) - Saragih, Elza Leyli Lisnora; Mulyadi, Mulyadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to describe the construction and how the formation pattern of serial verbs in Batak Toba language through X-bar theory. A qualitative descriptive method with data collection techniques using note-taking and interview techniques was used. Data were collected from interviews with native speakers and the text of Toba Batak language almanac. In analyzing the data, a method of distribution was employed. The results showed that the formation pattern of serial verbs in the Batak Toba language consisted of 4 types namely which were [transitive V1+ transitive V2], [transitive V1+intransitive V2], [intransitive V1+ transitive V2], and [intransitive V1 + intransitive V2]. The first type, [transitive V1+ transitive V2] is formed from the predicate that followed by the object + the predicate and followed by the object. The next formation, [V1 transitive + V2 intransitive] is formed from predicates followed by object + predicates and not followed by the object. The later type, [V1 intransitive + V2 transitive] is formed from predicates that not followed by object + predicates and followed by an object. Further, the last type, [intransitive V1 + V2] is formed from a predicate not followed by an object + a predicate and not followed by an object.